Investigation on the ZBG-functionality of phenyl-4-yl-acrylohydroxamic acid derivatives as histone deacetylase inhibitors. Issue 20 (15th October 2015) - Musso, Loana; Cincinelli, Raffaella; Zuco, Valentina; Zunino, Franco; Nurisso, Alessandra; Cuendet, Muriel; Giannini, Giuseppe; Vesci, Loredana; Pisano, Claudio; Dallavalle, Sabrina
Graphical abstract: Abstract: A series of alternative Zn-binding groups were explored in the design of phenyl-4-yl-acrylohydroxamic acid derivatives as histone deacetylase (HDAC) inhibitors. Most of the synthesized compounds were less effective than the parent hydroxamic acid. However, the profile of activity shown by the analog bearing a hydroxyurea head group, makes this derivative promising for further investigation.